Implementasi Pendekatan Stse-Ir Pada Perkuliahan Kimia Pangan Topik Karbohidrat Untuk Melatihkan Keterampilan Berpikir Evaluatif - Sofia Sofia; Maefa Eka Haryani; Rodi Edi (Chemistry Education Study Program Sriwijaya University, 2022)
The purpose of this study is to describe the implementation of the Science Technology Society Environment approach and reflective inquiry strategy (STSE-IR) in Food Chemistry on carbohydrate topics to practice Evaluative Thinking skills. This research was conducted at the Chemistry Education Study Program in one of the state universities in South Sumatra. The research subjects were students who took the Food Chemistry course in the odd semester of 2018/2019. Research data collection was carried out in August-November 2019. The type of research used was descriptive research. Researchers Obtain information from the implementation of chemistry lectures through observations and Student Work Sheets. The instruments used are observation sheets and Work Sheets Students. Data collection techniques through observation and analysis of Work Sheets documents. The results of the study are as follows. The steps for lectures on Carbohydrates by Lecturers who were observed by observers have been carried out according to the STSE-IR approach stage. The results of the student Work Sheets assessment showed that the average implementation of the STSE-IR approach was 86.15%. Carbohydrates Lecture using the STSE-IR Approach has trained students' evaluative thinking skills. The STSE-IR approach can be used on other topics in food chemistry and other interdisciplinary courses and other thinking skills.Keywords. STSE-IR Approach, Carbohydrates in Food Chemistry, Evaluative Thinking Skills